Duration of the pre‐diagnostic interval in medulloblastoma is subgroup dependent. Issue 7 (25th February 2014) - Ramaswamy, Vijay; Remke, Marc; Shih, David; Wang, Xin; Northcott, Paul A.; Faria, Claudia C.; Raybaud, Charles; Tabori, Uri; Hawkins, Cynthia; Rutka, James; Taylor, Michael D.; Bouffet, Eric
<x xml:space="preserve">Abstract</x> Background Children presenting with medulloblastoma have a wide range of initial presenting symptoms. However, the influence of underlying tumor biology on the initial presentation of medulloblastoma is currently unknown. In light of the recent discovery of distinct medulloblastoma subgroups, we sought to define the initial presentation of childhood medulloblastoma in a subgroup specific manner. Procedure We assembled a cohort of 126 medulloblastoma cases at the Hospital for Sick Children between 1994 and 2012 and determined subgroup affiliation using nanoString. Clinical details pertaining to the initial presentation were determined through a retrospective chart review. Results The median pre‐diagnostic interval across all medulloblastoma cases was 4 weeks (IQR: 4–12 weeks). Strikingly, when the pre‐diagnostic interval was then determined in a subgroup specific manner, cases with WNT and Group 4 tumors showed significantly longer median pre‐diagnostic intervals of 8 weeks compared to 2 weeks for SHH and 4 weeks for Group 3 (P = 0.0001). Younger age was significantly associated with a prolonged pre‐diagnostic interval (P = 0.02 for all). When stratifying by subgroup the association with age was only significant in Group 4 (P = 0.04 for Group 4). Improved survival was significantly associated with a longer pre‐diagnostic interval (P = 0.02), however is no longer significant when controlling for subgroup (P = 0.07). Conclusions The duration of the pre‐diagnostic interval in childhood medulloblastoma is highly subgroup dependent, further highlighting the clinical heterogeneity and biological relevance of the four principle subgroups of medulloblastoma. Pediatr Blood Cancer 2014;61:1190–1194. © 2014 Wiley Periodicals, Inc.